The Effect of Warm Water Compress on Back Pain Intensity in Pregnant Women in The Thirty Trimester - Fathiyati, Fathiyati; Sari, Dwinda; Saputri, Eneng Emi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pregnancy is a physiological thing that in the process will undergo adaptation changes both physiologically and psychologically. Changes in physiological adaptation will affect psychologic adaptation starting from the first trimester to the third trimester. This study aims to find out the effect of warm water compresses on back pain intensity in pregnant women in the third trimester in the independent practice of Midwife Siti Hapsah, S.Tr.Keb in 2024. The design of this study is by using the Quasy Experimental research method with a design used by one group of pre-test post-test with 53 respondents and data collection using observation sheets and then analyzed using non-parametric tests of the Wilcoxon test. The results of the study found that the most respondents were aged 20-35 years as many as 37 people (69.85), the most respondents' education was elementary school 17 people (32.15), respondents who did not work were 30 people (56.6%) and multipara 40 people (11.3%). The results of the analysis obtained a significance value of 0.000 which was smaller than the significance result of 5% (p-value = 0.000 <0.05) so the conclusion is that Ha is accepted, meaning that there is an effect of warm water compresses on the intensity of reducing back pain in pregnant women in the third trimester.